TENS improves CFL injury rat and regulates the intestinal microbiota - Min Miao; Tong Ma; Ran Chen; Kuan Geng; Zhiqiang Shen; Yan Sun (PLoS ONE, 2025)
Aim This study revealed the mechanism of transcutaneous electrical nerve stimulation (TENS) for improving the calcaneofibular ligament (CFL) injury rats by regulating the intestinal microbiota. Methods After 1, 2, and 3 weeks of TENS treatment, the improvement of CFL injury rats model and the expressions of IL-1β/NF-κB/IL-17 signaling pathway were measured. Then the intestinal microbiota was analyzed by 16S rDNA sequencing and its functions related to improve CFL injury rat were analyzed. Results TENS could improved the athletic ability of CFL injury rats and reduced the expressions of IL-1β/NF-κB by regulating the IL-17 signaling pathway. By 16S rDNA sequencing analysis, the TENS treatment improved the intestinal dysbacteriosisof CFL injury rats and decrease pathogenic bacteria Ruminococcus and Dubosiella. The changed intestinal microbiota maybe relative with the ankle injury, whereas the increase in probiotics (Bacteroides and Lactobacillus) was relative with anti-inflammation. Conclusion TENS could down-regulate the expressions of IL-1β/NF-κB to improve CFL injury rat. TENS could change the intestinal microbiota of CFL rats and the changed bacteria whose function related to anti-inflammation could improve CFL rat. The intestinal microbiota could become a potential treatment for CFL injury.